Migration of pediatric epidural catheters. Issue 6 (22nd January 2015) - Strandness, Thomas; Wiktor, Marisa; Varadarajan, Jaya; Weisman, Steven; Lonnqvist, Per‐Arne
Summary Background Postoperative pain control in the pediatric population frequently involves epidural catheters placed intraoperatively. A retrospective review of epidural catheter tip position was conducted by evaluation of routine chest anterior–posterior (A‐P) X‐rays obtained by the surgical and ICU teams. Methods Of the 174 pediatric epidural catheters placed during a 1‐year period at Children's Hospital of Wisconsin, 59 pediatric patients with chest X‐rays demonstrating epidural catheter tip on at least 2 days were reviewed. The change in epidural catheter position was then calculated. The overall reason for discontinuation of epidural analgesia in the larger population was also compiled. Results It was determined that epidural catheters migrated more frequently in patients <10 kg and 10–40 kg, when compared to those >40 kg P < 0.001. The average migration seen on X‐ray was 1.1 levels inward in those <40 kg and 0.3 levels inward in those >40 kg. The incidence of catheters discontinued secondary to falling out, or migrating in, was also increased in those patients <40 kg when compared to those >40 kg. Conclusion Results suggest that epidural catheters move inward more frequently and fall out more frequently in patients <40 kg.